Pengaruh Pengetahuan Dan Segmentasi Psikografis Terhadap Minat Menjadi Nasabah Pegadaian Syariah - Verranie, Syifa; Damayanti Rusmana, Fenny; Apriana, Agung (CV. ULIL ALBAB CORP, 2024)
In the current era, non-bank institutions finance is increasingly in demand because it can provide initial capital intake for people, especially those opening small and medium businesses, for example sharia pawnshops. And it is this psychological life skills factor that influences a person's decision to become a customer. This research aims to find out what factors make someone choose to become a sharia pawnshop customer. This research method adopts a quantitative approach, using statistical methods to analyze and measure the relationship between variables, as well as collecting data from various populations. The results of this research are that from the F test it is known that the calculated F is greater than (12,811 > 3.09). meaning that Knowledge (X1), Psychographic Segmentation (X2) have a simultaneous influence on Interest in becoming a customer (Y). Meanwhile, the Knowledge T Test (X1) shows that the calculated t value is greater than the t table (4,375 > 1.984). there is an influence of Knowledge (X1) on Interest in becoming a customer (Y). Psychographic Segmentation (X2) calculated t value is greater than t table (1.505 < 1.984). This means that there is no influence of Psychographic Segmentation (X1) on Interest in becoming a customer (Y).